Penguatan Kapasitas Kader Posyandu Mengenai PHBS sebagai Upaya Pencegahan Stunting di Sempadan Sungai Mahakam - Rina Tri Agustini; Lies Permana; Annisa Nurrachmawati (Cv. Utility Project Solution, 2023)
According to the 2021 Indonesia Nutrition Status Survey, the percentage of stunting cases in Kutai Kartanegara Regency is 26.4%, which is still above the national development target of 14%. Six out of ten villages in Sebulu District are stunting locus including in Sebulu Ilir Village and Segihan Village. One of the stunting preventions in the family setting that could be done is through partnerships, community empowerment, and Educational Information Communication (IEC) related to Clean and Healthy Behavior. This community service activity aims to establish a partnership with the public health center; increasing knowledge about clean and healthy behavior among posyandu cadres and mothers through IEC strategies and community empowerment. The method used were lecture and group discussion. The activities started with (1) preparation and coordination with the health center and village officials; (2) implementing IEC to increase the capacity of posyandu cadres; (3) cadres practice IEC for mothers of childen under five; (4) evaluation monitoring. The IEC results showed that cadres have increased their knowledge and are skilled at using flipcharts to carry out health education at posyandu. Cadres have also been able to carry out IEC with the small group discussion method and simulation targeting mothers of childen under five Follow-up activities have also been carried outt namely the implementation of IEC by cadres at posyandu.